POSTTREATMENT NEUROBLASTOMA MATURATION TO GANGLIONIC CELL TUMOR - M. V. Ryzhova (Opuholi Golovy i Šei, 2015)
Tumor cells can differentiate into more mature forms in undifferentiated or poorly differentiated tumors, such as medulloblastomas with increased nodularity, as well as neuroblastomas. The authors describe 2 cases of neuroblastoma maturation into ganglioneuroblastoma 5 months after chemotherapy in a 2-year-old girl and 3 years after radiotherapy in a 16-year-old girl.